Using a data driven approach for comprehensive Life Cycle Assessment and effective eco design of the Internet of Things: taking LoRa-based IoT systems as examples - Ernesto Quisbert-Trujillo; Panagiota Morfouli (Discover Internet of Things, 2023)
Abstract As we reach the limits of our current technologies and the number of connected devices grows, scientists put more efforts to estimate and reduce the ecological damage of the Internet of Things. Unfortunately, recent literature related to Life Cycle Assessment and eco design of IoT systems suffers from a major inconvenience so far: it does not put sensor data in the focus of attention. This paper aims to point out explicitly the essential role of this aspect for modeling reference flows, and demonstrate its relevance for appropriate environmental assessment and practical eco design. Also, it aims to illustrate that such modeling process must happen in a comprehensive way. For this, our work relies on a case study addressing smart metering, and we proceed as follows: based on available documentation and inspired by certain aspects of different technologies, we deduce the maximal capacities of key electronic components and construct an unfavorable data flow scenario, to get a rough idea of the reference flow and the long-term impact of our system during its use phase. Results from this procedure are later contrasted with results obtained from a packet traffic analysis, in which local and internet data flow are examined carefully. At the end, we verify the importance of sensor data theoretically and empirically, and we conclude that the reference flow and the impact contributors of a system could be affected not only by the local data transit but also by the complex interactions between edge devices and cloud resources. All our findings are discussed to nourish the state-of-the-art around the environmental impact of using full IoT systems and their sustainable design.